Analysis of Public Interest in Gold Installment Products at Bank Syariah Indonesia KCP Medan Tomang Elok - Hanifah Oktaviani Fakhri; Ahmad Perdana Indra (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
This research was based on the lack of public interest in saving gold at Bank Syariah Indonesia KCP Medan Tomang Elok. This research was conducted with the aim of knowing the reasons for the lack of public interest in saving gold at Bank Syariah Indonesia KCP Medan Tomang Elok. The design is field research. Data collection was carried out by field observations and literature review. The data were analyzed through a descriptive qualitative approach. The results showed that the public's interest in saving gold at Bank Syariah Indonesia KCP Medan Tomang Elok was still lacking. This is due to the lack of socialization to the community so that there is a lack of knowledge about the financing of gold installments which is very profitable, the community's economy is inadequate, the distance between the company and community settlements is far, besides this research also explains the investment opportunities contained in this product, namely the need customers, the benefits that come from investing in gold, the ease of buying and selling gold precious metals, rising gold prices that continue to improve with low competition. Those are some of the reasons why people are interested in taking the Gold Installment financing product at BSI KCP Medan Tomang Elok as a promising long-term investment.